ChemInform Abstract: Nucleophilic Bromodifluoromethylation of Iminium Ions. Issue 10 (March 2015) - Tsymbal, Artem V.; Kosobokov, Mikhail D.; Levin, Vitalij V.; Struchkova, Marina I.; Dilman, Alexander D.
Abstract An optimized one‐pot procedure for the title reaction is elaborated which includes intermediate formation of iminium electrophiles and difluorocarbene as reactive agents.